1989
DOI: 10.1161/01.cir.80.5.1148
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of patients with non-Q wave myocardial infarction. The critical role of ST segment depression. The Diltiazem Reinfarction Study Research Group.

Abstract: One-year follow-up data on 515 patients who survived hospitalization with MB-creatine kinase-confirmed, acute non-Q wave myocardial infarction were analyzed for factors related to mortality (n=57) and late reinfarction (n=64). Twelve of 24 analyzed variables were significantly associated with mortality. Those factors, which were independently predictive of mortality by Cox regression analysis, were persistent ST depression (p=0.0009), a history of congestive heart failure (CHF) (p=0.0069), older age (p =0.0128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…In a study of 515 survivors of hospitalization for NSTEMI, risk factors included persistent ST-segment depression, HF, advanced age, and ST-segment elevation at discharge. 682 Patients with all high-risk markers present had a 14-fold greater mortality rate than did patients with all markers absent. Elevated cardiac TnT levels have also been demonstrated to provide independent prognostic information for cardiac events at 1 to 2 years.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 96%
“…In a study of 515 survivors of hospitalization for NSTEMI, risk factors included persistent ST-segment depression, HF, advanced age, and ST-segment elevation at discharge. 682 Patients with all high-risk markers present had a 14-fold greater mortality rate than did patients with all markers absent. Elevated cardiac TnT levels have also been demonstrated to provide independent prognostic information for cardiac events at 1 to 2 years.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 96%
“…age, and ST-segment elevation at discharge. 788 Patients with all high-risk markers present had a 14-fold greater mortality rate than did patients with all markers absent. Elevated cardiac TnT levels have also been demonstrated to provide independent prognostic information for cardiac events at 1 to 2 years.…”
Section: Antioxidant Vitamins and Folic Acidmentioning
confidence: 96%
“…19,20) Several publications highlighted the prognostic value of ST segment depression in acute coronary syndromes (ACS). 21) ST segment depression is considered as one of the most important predictors of recurrent angina pectoris, reinfarction, and death in ACS. 5) Nyman and colleagues reported that patients with unstable angina and NSTEMI having ST segment depression on baseline admission ECG were at highest risk for cardiac death, MI, and severe angina pectoris with a follow-up of one year.…”
Section: Discussionmentioning
confidence: 99%
“…No significant relation could be found between ST segment resolution and these 5 factors. A possible clinical benefit of the appearance of ST segment resolution at the 72 nd hour can be speculated using the findings of the PRISM-PLUS trial, [13][14][15][16][17][18][19][20][21][22] which reported better outcomes compared to PRISM study where the tirofiban infusion was maintained during 72 hours in ACS compared to 48 hours in PRISM. 23) Patients who have invasive procedures seem to gain the most benefit from GP IIb/IIIa inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%